Maori Television: The First Ten Years - Smith, Jo (Auckland University Press, 2016)
Established in 2004, Maori Television has had a major impact on the New Zealand broadcasting landscape. But over the past year or so, the politics of Maori Television have been brought to the foreground of public consciousness, with other media outlets tracking Maori Television's search for a new CEO, allegations of editorial intervention and arguments over news reporting approaches to Te Kohanga Reo National Trust.Based on a Marsden Grant and three years of interviews with key stakeholders – staff, the Board, other media, politicians, funders and viewers – this is a deep account of Maori Television in its first ten years. Jo Smith argues that today's arguments must be understood within a broader context shaped by non-Maori interests. Can a Maori broadcaster follow both tikanga and the Broadcasting Standards Authority? Is it simply telling the news in Maori, or broadcasting the news with a Maori perspective? How can it support te reo Maori at the same time as appeal to all New Zealand? How does it function as the voice of its Maori stakeholders?Offering five frameworks to address the challenges of a Maori organisation working within a wider non-Maori context, this is a solidly researched examination of Maori Television's unique contribution to the media cultures of Aotearoa New Zealand.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des industries culturelles; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; Nouvelle-Zélande/Aotearoa (corpus analysé); Nouvelle-Zélande/Aotearoa (lieu de production du savoir); _Nettoyé

Numéro spécial : Kin constellations languages waters futures - Eshraghi, Leuli; Moulton, Kimberly (Artlink, 2020)
In this edition, we consider Ancestral materiality, intellectual traditions and expressions spanning the great oceans, skies and lands connecting the kin and Country of First Peoples from around the world. We see the artistic, economic and cultural paradigms as a reflection on life and death, on black holes and shining stars illuminated as constellations in the night skies from the times of our Ancestors and traced in the footprints made on the lands we travel.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice LGBTQ+; 5-Auteur.rice autochtone; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"–Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Section: 287 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Becoming our future: global indigenous curatorial practice - Nagam, Julie; Tamati-Quennell, Megan; Lane, Carly (ARP Books, 2020)
"This book investigates international Indigenous methodologies in art curatorial practice from the geographic spaces of Canada, Aotearoa (New Zealand) and Australia. From a perspective of Indigenous peoples important place within society, this collection explores how Indigenous art and culture operate within and from a structural framework that is unique and is positioned outside of the non-Indigenous cultural milieu. Through a selection of contributions, Becoming Our Future articulates this perspective, defines Indigenous curatorial practice and celebrates Indigenous sovereignty within the three countries. It begins to explore the connections and historical moments that draw Indigenous curatorial practices together and the differences that set them apart. This knowledge is grounded in continuous international exchanges and draws on the breadth of work within the field. With contributions by Nigel Borell, Nici Cumpston, Freja Carmicheal, Karl Chitham, Franchesca Cubillo, Léuli Eshraghi, Reuben Friend, Jarita Greyeyes, Heather Igloliorte, Jaimie Isaac, Carly Lane, Michelle LaVallee, Cathy Mattes, Bruce McLean, Kimberley Moulton, Lisa Myers, Julie Nagam, Wanda Nanibush, Jolene Rickard, Megan Tamati-Quennell, and Daina Warren."– Provided by publisher.
Section: 240 pages : illustrations (chiefly color) ; 26 cm
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Knowledge Positions in Aotearoa and Turtle Island Art Museums - Eshraghi, Leuli; Ash-Milby, Kathleen; Nuku, Maia; Borell, Nigel (Artlink, 2020)
Art, performance, and spoken or now written text, all belong to the same register of cultural practice in the First Nations I am familiar with or belong to: ceremony. This ceremonial register takes place in a set of spaces created to enact cultural responsibilities to place, people and balance. Galleries and museums, as sites of cultural production and presentation, have the potential to nurture new ceremonies and new working methods.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Haerenga Wairua: Spirit(ual) Journeys in Twenty-First-Century Māori Cinema - Walker-Morrison, Deborah (Canadian Journal of Film Studies, 2020)
Haerenga Wairua / Spiritual Journeys explore le cinéma maori en tant que 4e cinéma, dans son articulation de la spiritualité maorie comme un ensemble de croyances et de pratiques vivantes et d’une grande pertinence pour ce XXIe siècle. Après une brève description des termes et croyances clés, l’auteure analyse deux longs-métrages de fiction récents, The Strength of Water (Armagan Ballantyne, scr Briar Grace-Smith, NZ & Allemagne 2009) et The Pā Boys (Himiona Grace, NZ, 2014) comme emblématiques des pratiques cinématographiques autochtones, en ce qu’ils mettent fortement en avant différents niveaux et expériences de transformation spirituelle, via divers voyages au propre comme au figuré : voyages réels, voyages psychologiques ET expériences après la mort, donc voyages spirituels. Positionnant ces films dans le contexte des traditions spirituelles de narration littéraire et cinématographique, l’auteure explore les diverses techniques filmiques et cinématographiques mises en œuvre pour rendre l’expérience spirituelle, via le son et l’image, en mettant en évidence les liens avec la Terre, l’Eau et l’environnement naturel en tant qu’éléments spirituels et souvent surnaturels. Alors que ces derniers sont généralement interprétés par les critiques et chercheurs allochtones comme étant de l’ordre du fantastique, dans le discours établi du réalisme magique, l’auteure avance plutôt que les représentations autochtones ne peuvent être ni expliquées ni contenues de manière adéquate par ce terme, et propose à sa place celui de « réalisme spirituel autochtone ». L’auteure conclut en soulignant la pertinence de voix autochtones comme celles-là, qui expriment une spiritualité enracinée dans l’interdépendance de tous êtres et de toutes choses : force de guérison dans notre planète meurtrie.
Keywords: 1-Cinéma; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

How Aborigines Invented the Idea of Contemporary Art: Writings on Aboriginal Contemporary Art - McLean, Ian (Institute of Modern Art, 2011)
Chronicles the global critical reception of Aboriginal art since the early 1980s and argues for a re-evaluation of Aboriginal art's critical intervention into contemporary art.
OCLC: 762144288
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude de la réception; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Double Desire: Transculturation and Indigenous Contemporary Art - McLean, Ian (Cambridge Scholars Publishing, 2014)
ouble Desire challenges the tendency by critics to perpetuate an aesthetic apartheid between Indigenous and Western art. The double desire explored in this book is that of the divided but also amplified attractions that occur between cultural traditions in places where both indigenous and colonial legacies are strong. The result, it is argued, produces imaginative transcultural practices that resist the assimilation or acculturation of Indigenous perspectives into the dominant Western...
Section: xviii, 376 pages, 6 pages de planches : illustrations en partie en couleur ; 22 cm.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Possessions: Indigenous Art / Colonial Culture - Thomas, Nicholas (Thames and Hudson, 1999)
Tribal art has greatly inspired much 20th-century Western art. But is this a cross-cultural discovery to be celebrated, or another example of Western colonial appropriation? This work, focusing on countries such as Australia and New Zealand, argues that both views are too simplistic
Section: 304 p. : illustrations ; 24 cm
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Numéro spécial : Cinémas et médias autochtones dans les Amériques : récits, communautés et souverainetés - Dudemaine, André; Marcoux, Gabrielle; St-Amand, Isabelle (Canadian Journal of Film Studies, 2020)
Keywords: 1-Cinéma; 1-Histoire de l'art; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigenous and Decolonizing Studies in Education: Mapping the Long View - Tuhiwai Smith, Linda; Tuck, Eve; Yang, K. Wayne (Routledge, 2019)
Indigenous and decolonizing perspectives on education have long persisted alongside colonial models of education, yet too often have been subsumed within the fields of multiculturalism, critical race theory, and progressive education. Timely and compelling, Indigenous and Decolonizing Studies in Education features research, theory, and dynamic foundational readings for educators and educational researchers who are looking for possibilities beyond the limits of liberal democratic schooling. Featuring original chapters by authors at the forefront of theorizing, practice, research, and activism, this volume helps define and imagine the exciting interstices between Indigenous and decolonizing studies and education. Each chapter forwards Indigenous principles - such as Land as literacy and water as life - that are grounded in place-specific efforts of creating Indigenous universities and schools, community organizing and social movements, trans and Two Spirit practices, refusals of state policies, and land-based and water-based pedagogies.–publisher's description.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Video games and Indigenous education: Let’s bridge the ‘epistemology gap’ - Emery, Susannah; Habel, Chad (Ergo, 2017)
There are clear challenges posed by rural and remote education in Australia. These challenges are caused both by physical and material factors, but more importantly epistemological divisions that have created a separation between Indigenous and non-Indigenous worlds. Video games have the potential to bridge this epistemological gap by explicating the differences between different knowledge systems and engaging students in exploring these differences. Crucially, these projects need to be co-constructed to ensure that not only the representations of Indigenous people surpass some dubious traditions, but that different epistemologies are adequately framed. There is an urgent need for research-informed game-based learning projects to begin to address the ‘epistemology gap’ and the challenges faced by all Australians.
Number: 1
Keywords: 1-Jeux vidéo; 2-Humanités numériques; 2-Recherche-création; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; 5-Créatrice; _Nettoyé

Indigenous Art: New Media and the Digital - Igloliorte, Heather; Nagam, Julie; Taunton, Carla (Public, 2016)
Indigenous Art New Media and the Digital convenes leading scholars, curators, and artists from the Indigenous territories in Canada, the United States of America, Australia, and Aotearoa (New Zealand). It brings forth urgent conversations about resistance to colonial modernism, and highlights the historic and ongoing use of technology by Indigenous communities and artists as vehicles of resilience and cultural continuity. This issue ignites productive dialogue around the definitions of new and digital media art and practice-based work within the framework of Indigenous art and theory
Section: 215 pages : illustrations (principalement en couleur) ; 24 cm.
Keywords: 1-Histoire de l'art; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Decolonizing Methodologies: Research and Indigenous Peoples - Tuhiwai Smith, Linda (Zed books, 2012)
To the colonized, the term 'research' is conflated with European colonialism; the ways in which academic research has been implicated in the throes of imperialism remains a painful memory. This essential volume explores intersections of imperialism and research - specifically, the ways in which imperialism is embedded in disciplines of knowledge and tradition as 'regimes of truth.' Concepts such as 'discovery' and 'claiming' are discussed and an argument presented that the decolonization of research methods will help to reclaim control over indigenous ways of knowing and being. Now in its eagerly awaited third edition, this bestselling book includes a co-written introduction features contributions from indigenous scholars on the book's continued relevance to current research. It also features a chapter with twenty-five indigenous projects and a collection of poetry
Section: xv, 240 pages : illustrations ; 22 cm
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Méthodologie de recherche décoloniale; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé